Pengaruh Opini Auditor, Pergantian Manajemen dan Ukuran Perusahaan Klien Terhadap Auditor Switching - Michellia Ayu; Budi Kurniawan (UNIVERSITAS KALBIS, 2022)
This study provides an analysis to determine the effect of auditor's opinion, management turnover and company size on auditor switching. Audit opinion, company size and management turnover. The population in this study are all companies in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The number of research samples obtained was 52 manufacturing companies for the period 2015-2019, using the purposive sampling method and the amount of research data obtained was 260. The data analysis method used was quantitative logistic regression. The results of this study indicate that audit opinion and firm size have no effect on auditor switching, while management changes have an effect on auditor switching.